TRANSLATION SURFACES IN PSEUDO-GALILEAN SPACE WITH PRESCRIBED MEAN AND GAUSSIAN CURVATURES - Aydin, Muhittin Evren; Sepet, Sezin Aykurt; Bozok, Hulya Gun (Honam Mathematical Soc, 2022)
We study the translation surfaces in the pseudo-Galilean space with the condition that one of generating curves is planar. We classify these surfaces whose mean and Gaussian curvatures are functions of one variable.
Keywords: Pseudo-Galilean space; translation surface; Gaussian curvature; mean curvature